Efektivitas Terapi Relaksasi Otot Progresif pada Mahasiswa Tingkat Akhir yang Mengalami Stress di Program Studi Ilmu Keperawatan - Rustam, Zulis Noor Rafik; Suhermi, Suhermi; Alam, Rizqy Iftitah; Alam, Rizqy Iftitah (Window of Nursing Journal, 2020)
Covid 19 has brought many changes in human life. Currently, the campus is implementing an online learning system, aka online (in the network). This has an impact on final year students who are writing a thesis which will usually cause stress when compiling a thesis. Therefore, progressive muscle relaxation can reduce stress and learn how to relax tense muscles. The purpose of this study was to determine whether progressive muscle relaxation therapy can relieve or reduce stress levels in final year students. The research design used was quasi experimental. The research design used "pre test post test with control group design." The sample size obtained in this study was 30 respondents with a sampling technique carried out in the form of probability sampling with non-equivalent control group techniques. The data analysis used was the Wilcoxon test data analysis with a significance level of Î± = 0.05. If the value of Ï <0.05 then Ha is accepted. The research results from statistical analysis using the Wilcoxon test obtained the value of Ï = 0.001, where the value of Ï is smaller than the value of Î± = 0.05, so Ha is accepted. The results of the study proved that there was an effect of progressive muscle relaxation therapy on stress levels in final year students in the Indonesian Muslim University nursing study program. The conclusion of this study is that before being given progressive muscle relaxation therapy, the stress levels for final year students were moderate stress, severe stress and very heavy stress. Meanwhile, after being given progressive muscle relaxation therapy intervention, there was a decrease in stress levels, namely normal, mild stress and moderate stress.